Quantum Superposition of Media Messages: Assessing Sustenance and Collapse Trigger of Contradictory Beliefs Across Climate Change, Political Narratives, and AI Discourses in Nigeria - Samuel Sunday Ameh; Nathan Oguche Emmanuel; Precious Ojocheneyo Ugbaje; Nworie Chukwuebuka Stephen; Raphael Chijioke EZE (Informasi, 2026)
This study applies quantum cognition frameworks to investigate how Nigerian media audiences sustain contradictory beliefs ("superposition") across climate change, political narratives, and AI discourses. The study examines: (1) extent of superposition prevalence, (2) probabilistic belief distributions via quantum mathematics, (3) real-world collapse triggers, and (4) superposition duration. Using a mixed-design quasi-experiment, 800 Nigerian adults completed a Quantum Belief Scale (QBS) measuring probabilistic agreement with contradictory statements. Participants were stratified into intervention groups receiving domain-specific stimuli (IPCC reports, OECD guidelines, political endorsements) and a control. Experience Sampling Methodology tracked real-time belief fluctuations over 14 days. Quantum probability models and survival analyses were applied. Key findings reveal: Significant superposition across domains—political (56.7%), climate (50.1%), AI (45.2%)—challenging cognitive dissonance models. Climate-political beliefs showed strongest quantum correlations (concurrence=0.435±0.056), violating Bell inequalities (S>2), confirming non-classical interdependencies. Triggers like authoritative credible sources (e.g., NIMET climate data: 81.2% collapse rate) outperformed social media. Domain-specific interventions reduced superposition by 16–18% without cross-domain spillover. Also, the duration of median superposition stability lasted 8.4 days, extended among rural (9.1 days) and less educated (9.8 days) participants. Beliefs re-superposed within 18–24 hours post-collapse without reinforcement.